A major dyke swarm in the Ogaden region south of Afar and the early evolution of the Afar triple junction - Mège, D.; Purcell, P.; Bézos, A.; Jourdan, Fred; La, C. (2016)
© 2016 The Author(s).Geological mapping in the Ogaden region of SE Ethiopia, integrated with aeromagnetic data, has revealed a large dyke swarm extending SSE more than 600 km from the southern Afar margin across the Somali Plate to the Ethiopia-Somalia border. 40Ar/39Ar age dating shows that emplacement occurred at 24-27 Ma, contemporaneous with early rifting and dyking in the Red Sea. Slab-pull forces generated at the Zagros subduction zone strained the lithosphere in the Afro-Arabian plate, and dyking began to extend south from the Red Sea at c. 27 Ma, extending across Afar, fed by a plume-related magma source, rather than the rift-related source prevailing along the Red Sea. Immediately south of the Afar margin, the dyke system was emplaced along the Precambrian Marda Fault Zone, and the continuation across the Ogaden may have been controlled by lithospheric weakness associated with a splay of the Marda Fault. We suggest that the Ogaden Dyke Swarm is a zone of crustal dilation continuing the Red Sea trend across the Horn of Africa and constituting the original third 'arm' of the Afar triple junction. Geochemical and geochronological analyses indicate that basaltic outpourings from the Ogaden Dyke Swarm flowed at least as far east as the Ethiopia-Somalia border and emanated from the same magma source as the Ethiopian flood basalts, which had erupted earlier at c. 30 Ma. Dykes are emergent only occasionally and are marked at the surface by linear sand-filled troughs varying from 2 to 20 m deep caused by tensional collapse above the dyke tip. Magnetic anomalies associated with the dykes vary in width up to 1 km and likely identify dyke zones.